2015
DOI: 10.1051/0004-6361/201424790
|View full text |Cite
|
Sign up to set email alerts
|

Planckintermediate results

Abstract: Planck intermediate results XXVII. High-redshift infrared galaxy overdensity candidates and lensed sources discovered by Planck and confirmed by Herschel-SPIRE

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Throughout the paper we assume flatness, include massive neutrinos with a normal mass hierarchy (dominated by the heaviest neutrino mass eigenstate), and model DE as a fluid described by three quantities, namely: a constant equation of state w, a constant sound speed c 2 s , and a DE anisotropic stress π de . We will carry out the analysis for two fiducial models consistent with both DES and Planck [3,42]. Cosmological parameters for both fiducial models will only differ in the dark energy anisotropic stress model employed and the sound speed of DE perturbations.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the paper we assume flatness, include massive neutrinos with a normal mass hierarchy (dominated by the heaviest neutrino mass eigenstate), and model DE as a fluid described by three quantities, namely: a constant equation of state w, a constant sound speed c 2 s , and a DE anisotropic stress π de . We will carry out the analysis for two fiducial models consistent with both DES and Planck [3,42]. Cosmological parameters for both fiducial models will only differ in the dark energy anisotropic stress model employed and the sound speed of DE perturbations.…”
Section: Methodsmentioning
confidence: 99%
“…with continuum spectra peaking between 353 and 857 GHz, consistent with redshifts z > 2 for typical dust emission spectra. Herschel/SPIRE follow-up of 234 Planck targets with such colours showed that almost all of them correspond to strong over-densities of red 350 and 500 µm sources in comparison to reference SPIRE fields [92]. Further investigations of Planck proto-cluster candidates were carried out by refs.…”
Section: Early Phases Of Cluster Evolutionmentioning
confidence: 99%
“…DSFGs have now been found in a range of cluster environments, from extremely large proto-clusters on angular scales > 10 arcminutes (Dannerbauer et al 2014;Casey et al 2015;Casey 2016), to scales similar to those of the Planck HFI beam (Herranz et al 2013;Clements et al 2014;Planck Collaboration et al 2016, 2015a, to > 10 sources on ∼ 20 arcsecond scales (Oteo et al 2017a). The existence of many physically associated DSFGs is surprising; simulations expect these sources to be physically unassociated (Hayward et al 2013;Cowley et al 2014), and without a mechanism for triggering several DSFGs simultaneously or a longer duty cycle (Emonts et al 2016;Dannerbauer et al 2017;Oteo et al 2017b), we would not expect to observe several physically associated DSFGs at once (Casey 2016).…”
Section: The Nature Of Our Proto-cluster Candidatesmentioning
confidence: 99%
“…Several authors have already found plausible high redshift clusters using the Planck data (Herranz et al 2013;Clements et al 2014;Baes et al 2014;Planck Collabo-ration et al 2016, 2015a, with a variety of approaches. Both Herranz et al (2013) and Clements et al (2014) performed similar cross-matches between Herschel and Planck in order to search for clusters of DSFGs.…”
Section: Introductionmentioning
confidence: 99%